Hydrogen peroxide route to Sn-doped titania photocatalysts - Štengl, Václav (BioMed Central, 2012)
BACKGROUND: The work aims at improving photocatalytic activity of titania under Vis light irradiation using modification by Sn ions and an original, simple synthesis method. Tin-doped titania catalysts were prepared by thermal hydrolysis of aqueous solutions of titanium peroxo-complexes in the presence of SnCl(4) or SnCl(2) using an original, proprietary "one pot" synthesis not employing organic solvents, metallo-organic precursors, autoclave aging nor post-synthesis calcination. The products were characterized in details by powder diffraction, XPS, UV–vis, IR, and Raman spectroscopies, electron microscopy and surface area and porosity measurements RESULTS: The presence of tin in synthesis mixtures favors the formation of rutile and brookite at the expense of anatase, decreases the particle size of all formed titania polymorphs, and extends light absorption of titania to visible light region >400 nm by both red shift of the absorption edge and introduction of new chromophores. The photocatalytic activity of titania under UV irradiation and >400 nm light was tested by decomposition kinetics of Orange II dye in aqueous solution CONCLUSIONS: Doping by Sn improves titania photoactivity under UV light and affords considerable photoactivity under >400 nm light due to increased specific surface area and a phase heterogeneity of the Sn-doped titania powders.